Scoutmaster Jan Poplewski – An Example of Attributing Financial Crime to Opponents of the Communist Regime - Kuświk, Bartosz (Studia Historiae Oeconomicae, 2016)
The article describes a failed attempt to attribute financial crime – embezzlement of the money belonging to the Greater Poland Headquarters of the Local Council of the Polish Scouting and Guiding Association – to scoutmaster Jan Poplewski. However, from the very beginning, the security services were interested in his anti-systemic activity, i.e. inspiring illegal activities among young scouts in the Stalinist period. This story serves as an example for exploring the underresearched problem of attributing various crimes to the opponents of the system, in order to discredit them and use this fact for propaganda purposes. The scale of this problem is impossible to estimate at present, but sometimes it is possible to describe individual cases – for example the case of scoutmaster Jan Poplewski.